Pemberian Auksin dengan Berbagai Panjang Stek untuk Memacu Pertumbuhan pada Pembibitan Tanaman Alpukat (Persea americana Mill) - Muhammad Hafiz Alfiansyah; Aisyah Lubis; Farida Hariani (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2026)
Using Avocado (Persea americana Mill.) is a strategic horticultural commodity with high economic value and promising market prospects. Vegetative propagation through stem cuttings is the preferred method for producing quality seedlings, but requires optimization of growth hormone application and appropriate planting material dimensions. This study aimed to analyze the effects of Auxin application and cutting length variation on avocado seedling development. The research used a Randomized Complete Block Design (RCBD) factorial with two factors and three replications. The first factor was Auksin concentration (A? = control, A? = 200 mg 5ml-1, A? = 250 mg 5ml-1, A? = 300 mg 5ml-1). The second factor was cutting length dimension (B? = 15 cm, B? = 20 cm, B? = 25 cm). Variables evaluated included shoot formation success rate, leaf quantity, and number of shoots per sample unit. Variance analysis showed that Auxin application and cutting dimension variation did not provide significant effects on all observation variables. The interaction between both factors also showed no statistically significant effect. Suboptimal microclimatic conditions throughout the research period were estimated to be the dominant factor affecting treatment response.